Maternal Preeclampsia and Neonatal Outcomes - Carl H. Backes; Kara Markham; Pamela Moorehead; Leandro Cordero; Craig A. Nankervis; Peter J. Giannone (Journal of Pregnancy)
Preeclampsia is a multiorgan, heterogeneous disorder of pregnancy associated with significant maternal and neonatal morbidity and mortality. Optimal strategies in the care of the women with preeclampsia have not been fully elucidated, leaving physicians with incomplete data to guide their clinical decision making. Because preeclampsia is a progressive disorder, in some circumstances, delivery is needed to halt the progression to the benefit of the mother and fetus. However, the need for premature delivery has adverse effects on important neonatal outcomes not limited to the most premature infants. Late-preterm infants account for approximately two thirds of all preterm deliveries and are at significant risk for morbidity and mortality. Reviewed is the current literature in the diagnosis and obstetrical management of preeclampsia, the outcomes of late-preterm infants, and potential strategies to optimize fetal outcomes in pregnancies complicated by preeclampsia.